2012
DOI: 10.7183/0002-7316.77.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Linking Bones and Stones: Regional Variation in Late Paleoindian Cody Complex Land Use and Foraging Strategies

Abstract: AbstractUsing lithic and faunal data from 33 Cody complex (10,000–860014C years B.P.) components from the northern Great Plains, this study explores how Paleoindian land use and foraging strategies varied in relation to resource structure at the regional scale. The analysis of regional-scale faunal and lithic data was undertaken to demonstrate how disparate but related datasets must be considered together to develop a more complete understanding of hunter-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…As discussed previously (Hill and Knell 2013;Knell and Hill 2012), foragers and farmers would have found habitats to be quite different in terms of resource availability, abundance, and seasonal and spatial predictability. Mountains and foothills and alluvial valleys were likely calorie-rich areas with highly predictable and abundant biotic resources, and good sources of valuable abiotic resources (i.e., water, wood, and tool stone).…”
Section: Methodsmentioning
confidence: 73%
See 3 more Smart Citations
“…As discussed previously (Hill and Knell 2013;Knell and Hill 2012), foragers and farmers would have found habitats to be quite different in terms of resource availability, abundance, and seasonal and spatial predictability. Mountains and foothills and alluvial valleys were likely calorie-rich areas with highly predictable and abundant biotic resources, and good sources of valuable abiotic resources (i.e., water, wood, and tool stone).…”
Section: Methodsmentioning
confidence: 73%
“…In this study, we evaluated this hypothesis using a large dataset, finding no support for such a unidirectional intensification over time. and habitat differences in prey availability (e.g., Hill 2008;Knell and Hill 2012;Otárola-Castillo 2016). This study also sought to compare the Great Plains Paleoindian prey choice patterns we observed in our earlier work to evidence later in time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned earlier, obsidian was the most commonly used raw material for manufacturing projectile points in all of the regions studied. Given the importance of projectiles points for the survival of hunter‐ gatherer populations, the provisioning of obsidian must have been planned, if not scheduled (Knell & Hill, ). Because these plateaus are inaccessible during winter, the concomitant circulation of this rock would have been mainly during spring and summer.…”
Section: Discussionmentioning
confidence: 99%